Design and Development of Android-Based E-Modul Application to Improve Prosocial Early Children by Family - Setiawati; Asrul Huda; Ismaniar; Noper Ardi, (International Journal of Online and Biomedical Engineering (iJOE), 2023)
The aim of this research is to address the issue of low prosocial behavior in children, both at home and in public spaces. This was identified through observations and interviews with parents, who believe that the lack of their participation in their children’s prosocial development is due to their limited understanding. To improve early childhood prosocial behavior, the research team developed an Android-based E-Module that is practical and user-friendly, as well as accessible to a wider audience. This type of research is referred to as development research. The study’s objective is to design an Android-based E-Module application that can improve early childhood prosocial behavior within families. The ADDIE Model development method was utilized, with a survey conducted to assess the application’s validity, which was further validated by multiple experts. The results showed that the Android-based E-Module application’s validation test was deemed valid, and can be concluded that it is a useful tool to enhance early childhood prosocial behavior within families, specifically in the city of Padang.